Syphilitic hepatitis: An uncommon manifestation of a common disease - Sukriti Baveja; Shilpa Garg; Amol Rajdeo (Wolters Kluwer Medknow Publications, 2014)
Hepatitis being first manifestation of secondary syphilis is rare. Here in we report a case of 39 years old male who was being treated for hepatitis and presented to us subsequently with itchy maculopapular rash. Venereal disease research laboratory (VDRL) titre was 1:16. Treponema pallidum hemagglutination assay (TPHA) was positive. He was treated with intramuscular Benzathine Penicillin. His hepatitis improved rapidly.